Preparation method and application of double-ion co-pre-embedded VO2 material
By pre-embedding Ca2+ and Sr2+ ions in VO2 positive electrode material, the problem of slow Zn2+ ion transmission kinetics and poor crystal structure frame stability in VO2 positive electrode material in zinc ion batteries is solved, and the material's high zinc storage capacity, excellent rate performance and long cycle life are achieved.
Patent Information
- Application Number
- CN202510077869.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-29
AI Technical Summary
In zinc ion batteries, the existing VO2 positive electrode materials have poor rate performance and unsatisfactory cycle life due to the slow transmission kinetics of Zn2+ ion and poor stability of the crystal structure frame.
The preparation method of dual-ion pre-embedded VO2 material is adopted. By pre-embedded Ca2+ and Sr2+ ions in VO2, the crystal structure and morphological structure of the material are regulated, and the Zn2+ ion transport dynamics and the stability of the crystal structure frame are optimized.
The zinc storage capacity, rate performance and cycle stability of CaSr-VO2 materials are significantly improved, and can maintain high specific capacity and ultra-long-lasting cycle stability under high current density.
Smart Images

Figure CN119898816A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy technology, specifically to a dual-ion co-embedded VO 2 Preparation methods of materials and their applications. Background Art
[0002] With the progress of economy and technology, people's demand for energy is also increasing. The excessive consumption of traditional energy has led to increasingly prominent environmental degradation problems, which has promoted the development of new clean energy and efficient electrochemical energy storage devices. The use of new clean energy such as solar energy and wind energy can effectively reduce carbon emissions and achieve the "dual carbon" strategy. However, new clean energy has problems such as volatility and intermittency, and cannot be directly integrated into the power grid. Efficient and stable energy storage systems can effectively regulate the instability of clean energy, realize the "peak shaving and valley filling" of the power grid, reduce the peak load of the power grid, increase the valley load, smooth the load curve, increase the load rate, reduce the power load demand, reduce the investment in generator sets and stabilize the operation of the power grid.
[0003] At present, the batteries used in stationary energy storage systems are mainly lithium-ion batteries (LIBs), but their flammable organic electrolytes pose safety risks and environmental pollution. In order to overcome these problems, researchers have worked hard to develop advanced energy storage devices, including lithium-sulfur batteries, other alkali metal ions (Na + and K + ) batteries, and some multivalent ions (Zn 2+ ,Mg 2+ , Ca 2+ and Al 3+ ) batteries, etc. In recent years, sodium ion, potassium ion and other batteries have gradually appeared in people's field of vision, but there are still many shortcomings compared with lithium ion batteries. The ideal battery system should use cheap and environmentally friendly electrode materials, with excellent rate performance, high energy density, and ultra-long cycle stability. However, while pursuing these electrochemical properties and economic benefits, the safety performance of the battery is always the primary consideration. Only by ensuring the safety of the battery can we further promote its wide application in various fields and promote commercialization.
[0004] Among the numerous electrochemical energy storage devices, the most common ones are composed of a zinc metal anode, a near-neutral aqueous electrolyte, a separator, and a Zn 2+ Aqueous zinc-ion batteries (AZIBs) composed of embedded / extracted cathode materials have attracted great research interest from scholars at home and abroad due to their advantages such as high safety, environmental friendliness, flexible packaging conditions, and low manufacturing cost. In addition, zinc-ion batteries have a high theoretical specific capacity (820mAh g -1), suitable redox potential (-0.76V vs. SHE) and abundant zinc resources are considered to have broad application prospects in smart grids and large-scale energy storage devices, and are also considered to be one of the energy storage devices that may supplement lithium-ion batteries in the future. Vanadium-based and manganese-based oxides are common positive electrode materials for aqueous zinc-ion batteries. Manganese-based oxides have high discharge voltage (1.2-1.4V vs. Zn 2+ / Zn), high discharge capacity (>200mAh g -1 ) and low cost, and is considered to have the potential for industrial-scale use. 3+ To V 5+ ), high zinc storage capacity and theoretical capacity, and diverse crystal structures have attracted widespread attention. However, high charge density Zn 2+ During the insertion / extraction process, ions usually generate strong electrostatic interactions with positive electrode materials, resulting in slow ion transport kinetics. In addition, problems such as manganese / vanadium dissolution, crystal structure collapse, and parasitic side reactions lead to rapid battery capacity decay, hindering its further commercial application. Therefore, the development of fast Zn 2+ High-performance cathode materials that store and stabilize crystal structures are key to the development of aqueous zinc-ion batteries.
[0005] Metastable VO in monoclinic system 2 (B) It has an open tunnel-like structural framework, a twisted VO 6 Octahedral composition, its special one-dimensional tunnel structure in Zn 2+ The ion insertion / extraction cycle shows good lattice stability and provides one-dimensional Zn 2+ transmission channel, and the larger tunnel structure provides sufficient Zn 2+ Embedded space, so that it has a higher specific capacity and better rate performance. However, VO 2 The stability of the tunnel structure framework of (B) is still challenged during the cyclic charge and discharge process, resulting in capacity decay. The relatively fixed tunnel size also affects the Zn 2+ Ion transport rate, V 3+ / V 4+ The lower redox potential limits its zinc storage capacity and other issues. The above key issues will eventually lead to VO 2 (B) The capacity of the positive electrode material decays rapidly during long-cycle charge and discharge, which is far from the requirements for the commercialization of zinc-ion batteries. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of this application is to provide a dual ion co-pre-embedded VO 2 Preparation method of materials and application thereof to solve the problem of VO2 The positive electrode material is used in zinc ion batteries due to the 2+ Disadvantages such as slow ion transfer kinetics and poor crystal structure framework stability lead to problems such as poor rate performance and unsatisfactory cycle life of the battery.
[0007] In order to solve the above technical problems, this application adopts the following technical solutions:
[0008] A dual-ion co-pre-embedded VO 2 The method for preparing the material specifically comprises the following steps:
[0009] Step 1: dissolving vanadium pentoxide in deionized water, adding calcium sulfate and strontium sulfate, and continuously stirring to obtain a mixed solution; wherein the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is (10-50):1:1;
[0010] Step 2: adding ethylene glycol to the mixed solution obtained in step 1; wherein the molar ratio of the added amount of ethylene glycol to the vanadium pentoxide is 95:1 to 105:1;
[0011] Step 3: placing the mixture obtained in step 2 in an autoclave and reacting at 160° C. to 200° C. for 10 h to 14 h;
[0012] Step 4: Wash the product obtained from the reaction in step 3 to obtain CaSr-VO 2 Material.
[0013] Preferably, in step 1, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is (10-20):1:1.
[0014] Preferably, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is 20:1:1.
[0015] Preferably, the CaSr-VO 2 The material has a long and thin ribbon-like morphology.
[0016] Preferably, in step 3, the reaction temperature is 180° C. and the reaction time is 12 h.
[0017] The present application also provides a dual ion co-pre-embedded VO 2 Application of materials, CaSr-VO prepared by the above preparation method 2 The material is used as the positive electrode material of aqueous zinc-ion batteries.
[0018] Compared with the prior art, this application has the following beneficial effects:
[0019] 1. The method described in this application does not require VO 2 Under the premise of destroying the crystal structure framework of the material, it is found that by regulating Ca2+ and Sr 2+ The ratio of the co-pre-embedded CaSr-VO 2 The material morphology changes significantly, showing a uniform, elongated one-dimensional ribbon morphology, which not only increases the specific surface area of the material, thereby providing more electrochemical reaction sites, making the material have good zinc storage capacity; but also can optimize the Zn 2+ The kinetic behavior of ion transport can enhance the zinc storage rate performance of the material.
[0020] 2. The present application further found that Ca 2+ and Sr 2+ The co-pre-embedding did not damage the crystal structure framework of the material, which indicates that the dual ion co-pre-embedding process of the method described in the present application has a positive effect on the crystal structure stability of the material. 2+ / Sr 2+ Together they act as "pillars" to ensure the stability of the tunnel structure framework, which helps to avoid Zn 2+ During the ion insertion / extraction cycle, the crystal structure collapses or undergoes phase changes, thereby improving the zinc storage cycle stability of the material.
[0021] 3. CaSr-VO prepared by the method described in this application 2 The material has significant advantages in the application of positive electrode materials for aqueous zinc-ion batteries. 2 The material still exhibits a high specific capacity at high current density; it exhibits excellent cycle life and coulombic efficiency at both large and small current densities, especially at high current density, it has ultra-long-lasting cycle stability, which is mainly attributed to the Ca 2+ and Sr 2+ Co-pre-embedded Zn optimized material 2+ The ion transport kinetics and crystal structure framework show that the CaSr-VO prepared by the method described in this application 2 The positive electrode material has excellent electrochemical properties such as specific capacity, rate performance and cycle stability, which provides a way to develop high-performance positive electrode materials for zinc-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Example CaSr-VO synthesized with different concentrations of pre-embedded ions 2 And the comparative example VO 2 、Ca-VO 2 、Sr-VO 2 XRD patterns; wherein a is the pre-embedded ion with different concentrations synthesized in Examples 1 to 3 (CaSr-VO 2 ) and Comparative Example 1 (VO 2) of the embodiment 2 (CaSr-VO 2 ), Comparative Example 2 (Ca-VO 2 ) and Comparative Example 3 (Sr-VO 2 )’s XRD patterns.
[0023] Figure 2 The CaSr-VO synthesized under different synthesis temperature and synthesis time conditions 2 XRD patterns of materials; wherein, a is a comparison of the XRD patterns of Example 2 and Comparative Examples 4 to 5 synthesized under different synthesis temperature conditions; b is a comparison of the XRD patterns of Example 2 and Comparative Examples 6 to 7 synthesized under different synthesis time conditions.
[0024] Figure 3 This is the SEM image of Comparative Example 7.
[0025] Figure 4 is a comparison of the surface morphology of the embodiment and the comparative example; wherein a is the surface morphology of the comparative example VO 2 a is the SEM image of Example 1; b is the SEM image of Example 2; d is the SEM image of Example 3.
[0026] Figure 5 is the XPS spectrum of the embodiment; wherein a is the XPS full spectrum of Example 2, b is the Ca 2p high-resolution XPS spectrum of Example 2, and c is the Sr 3d high-resolution XPS spectrum of Example 2.
[0027] Figure 6 The electrochemical performance of the embodiments and comparative examples as positive electrode materials for zinc ion batteries is compared; wherein a is the rate performance; b is the cycle stability at 0.1 A / g; and c is the cycle stability at 5.0 A / g.
[0028] Figure 7 The electrochemical performance of two ion co-pre-embedded (example) and single ion pre-embedded (comparative example) as positive electrode materials for zinc ion batteries is compared; wherein a is the rate performance; b is the cycle stability at 1.0 A / g.
[0029] Figure 8 The figure shows the electrochemical performance comparison of the comparative examples synthesized under different synthesis temperature and synthesis time conditions as positive electrode materials for zinc ion batteries; wherein a is the rate performance synthesized under different synthesis temperature conditions; and b is the rate performance synthesized under different synthesis time conditions. DETAILED DESCRIPTION
[0030] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0031] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0032] 1. A dual-ion co-embedded VO 2 Material preparation method
[0033] Step 1: dissolving vanadium pentoxide in deionized water, adding calcium sulfate and strontium sulfate, and continuously stirring to obtain a mixed solution; wherein the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is (10-50):1:1;
[0034] Step 2: adding ethylene glycol to the mixed solution obtained in step 1; wherein the added amount of ethylene glycol is (95:1) to (105:1);
[0035] Step 3: placing the mixture obtained in step 2 in an autoclave and reacting at 160° C. to 200° C. for 10 h to 14 h;
[0036] Step 4: Wash the product obtained from the reaction in step 3 to obtain CaSr-VO 2 Material.
[0037] This application will be VO 2 When applied to the positive electrode materials of aqueous zinc-ion batteries, it was found that VO 2 Vanadium dissolution occurs in aqueous electrolytes; VO 2 During long cycle charge and discharge, its crystal structure framework may change, resulting in poor cycle stability; VO 2 Cathode Materials and Zn 2+ The ions will produce strong electrostatic effects, hindering the Zn 2+ In view of these technical problems, the present invention proposes to use a dual metal ion co-pre-embedding strategy to regulate VO 2 The crystal structure and morphology of the material are expected to improve its electrochemical performance. Therefore, the present invention screens the co-pre-embedded metal ions. From the perspective of ion radius, Ca 2+ and Sr 2+ The ionic radius of V 4+ The ionic radius is large, and this large ionic radius is predicted to be able to 2An appropriate amount of lattice distortion is introduced into the lattice; considering the electronegativity, Ca 2+ and Sr 2+ The electronegativity of Ca is relatively low, which enables them to provide additional charge compensation during the pre-embedding process, helping to maintain the electrical neutrality of the material, thereby improving the crystal structure stability and electrochemical performance of the material; in terms of lattice matching, Ca 2+ and Sr 2+ The ionic radius of VO 2 The lattice oxygen ion radius is relatively matched, which helps to stabilize the pre-embedded ions in VO 2 In the lattice, excessive lattice distortion is avoided, thereby destroying the crystal structure framework. The present application also considers other metal ions, which are similar to Ca 2+ and Sr 2+ Among similar metal ions, although Ba 2+ The ionic radius of Mg is also large, but an excessively large ionic radius may cause serious lattice distortion, thus affecting the crystal structure stability of the material. 2+ and Be 2+ The ionic radius of Mg is small, and it cannot provide sufficient lattice distortion after embedding, resulting in insignificant morphology control effect. 2+ and Be 2+ The electronegativity of Ca is high, which may affect the electrical neutrality of the material and thus its electrochemical performance. 2+ and Sr 2+ ions are co-pre-embedded. The present application further found that the CaSr-VO prepared in the present application 2 The XRD diffraction peaks of the material are similar to those of VO 2 The standard card (PDF#05-4530) of the crystal structure is completely matched and belongs to the monoclinic system, which indicates that Ca 2+ and Sr 2+ Ions in the absence of VO 2 The crystal structure framework of the VO was successfully pre-embedded under the premise of causing great damage to the 2 More surprisingly, as Ca 2+ and Sr 2+ With the increase of the co-pre-embedded concentration, the morphology of the material changes unexpectedly, from the original agglomerated, particle-accompanied rod-like morphology to a uniform, elongated ribbon-like morphology. This series of microscopic changes also makes CaSr-VO 2 The electrochemical performance of the material is improved.
[0038] In some embodiments of the present application, in step 1, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate can be (10-50):1:1. However, the present application found that when the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is 50:1:1, CaSr-VO 2The morphology of the material is similar to that of pure VO 2 Compared with the above, the change is not significant, which indicates that although the pre-embedding can be successfully performed at this molar ratio, the pre-embedding process has little effect on the material morphology and is not enough to change its morphology. As the molar ratio gradually changes, the concentrations of calcium sulfate and strontium sulfate gradually increase. When the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is 25:1:1, CaSr-VO 2 The morphology of the material is similar to that of pure VO 2 Compared with the beginning, the slender ribbon-like morphology structure increased significantly; and as the molar ratio was adjusted to 20:1:1, the change in morphology structure became more obvious, and it has completely shown the difference with pure VO 2 , and the completely different morphological characteristics when the molar ratio is 50:1:1. 2 The material exhibits a uniform and unique elongated ribbon morphology. When the molar ratio continues to be adjusted toward the value of 10:1:1, the obtained CaSr-VO 2 The material still presents a unique elongated ribbon morphology. Therefore, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate can be 10:1:1, 15:1:1, 20:1:1, 25:1:1, 50:1:1, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any other ranges.
[0039] In some embodiments of the present application, in step 3, the reaction temperature is 180°C and the reaction time is 12 hours. If the reaction temperature is too high, VO will not be generated. 2 If the reaction time is too short, the material's crystallinity will be reduced, while if the reaction time is too long, the material's morphology will be affected.
[0040] 2. A dual-ion co-embedded VO 2 Application of materials
[0041] The CaSr-VO prepared by the preparation method described in this application 2 The material is used as the positive electrode material of aqueous zinc-ion batteries.
[0042] 3. Examples and Comparative Examples
[0043] Example 1
[0044] Step 1: Dissolve vanadium pentoxide in deionized water, add calcium sulfate and strontium sulfate, and continue stirring to obtain a mixed solution; wherein the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is 50:1:1.
[0045] Step 2: Add ethylene glycol to the mixed solution obtained in step 1; wherein the amount of ethylene glycol added is 2 O5 The molar ratio is 100:1;
[0046] Step 3: The mixed solution obtained in step 2 was transferred to an autoclave and reacted at 180° C. for 12 hours.
[0047] Step 4: The product obtained in step 3 is washed with deionized water and ethanol, centrifuged and dried to obtain the CaSr-VO 2 25-1 material. 25-1 refers to V 2 O 5 The molar ratio of the total amount of the co-pre-embedded diions is 25:1.
[0048] Example 2
[0049] The method was adjusted based on Example 1, except that the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate was 20:1:1. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 10-1.
[0050] Example 3
[0051] The method was adjusted based on Example 1, except that the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate was 10:1:1. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 5-1.
[0052] Comparative Example 1
[0053] The method is adjusted based on Example 1, except that calcium sulfate and strontium sulfate are not added. The other steps are exactly the same, and the prepared material is VO 2 .
[0054] Comparative Example 2
[0055] The method was adjusted based on Example 1, except that the molar ratio of vanadium pentoxide to calcium sulfate was 10:1, and strontium sulfate was not added. The other steps were exactly the same, and the prepared material was recorded as Ca-VO 2 10-1.
[0056] Comparative Example 3
[0057] The method was adjusted based on Example 1, except that the molar ratio of vanadium pentoxide to strontium sulfate was 10:1, and calcium sulfate was not added. The other steps were exactly the same, and the prepared material was recorded as Sr-VO 2 10-1.
[0058] Comparative Example 4
[0059] The method was adjusted based on Example 2, except that step 3 was carried out at 140°C for 12 hours. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 140℃.
[0060] Comparative Example 5
[0061] The method was adjusted based on Example 2, except that step 3 was carried out at 210°C for 12 hours. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 210℃.
[0062] Comparative Example 6
[0063] The method was adjusted based on Example 2, except that step 3 was carried out at 180°C for 6 hours. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 6h.
[0064] Comparative Example 7
[0065] The method was adjusted based on Example 2, except that step 3 was carried out at 180°C for 24 hours. The other steps were exactly the same, and the prepared material was recorded as CaSr-VO 2 24h.
[0066] 4. Performance Comparison
[0067] 1. Crystal structure and morphology
[0068] Figure 1 a is the CaSr-VO synthesized with different concentrations of pre-embedded ions 2 Materials and Comparative Examples VO 2 The XRD patterns of the three groups of Examples 1 to 3 and the one group of Comparative Example 1 all have the same diffraction peaks as VO 2 The standard card (PDF#05-4530) of is corresponding, belonging to the monoclinic system. Further comparison shows that for Examples 1 to 3, with the increase of the pre-embedded ion concentration, the position of the main peak does not change significantly, which indicates that the use of Ca 2+ and Sr 2+ The regulation of co-preembedded ions did not cause significant damage to the crystal structure framework of the material, but the position and intensity of the secondary peaks changed, which also indicates that the change in the concentration of pre-embedded ions has a certain impact on the microstructure of the material.
[0069] Figure 1 b is single Ca 2+ or Sr 2+The XRD patterns of pre-embedded comparative examples 2 to 3 and embodiment 2 show that the diffraction peaks are consistent with VO 2 Corresponding to the standard card, the position of the main peak has not changed significantly, but the position and intensity of the secondary peak have changed, which also shows that the pre-embedded different metal ions have a certain influence on the microstructure of the material.
[0070] Figure 2 a-2b correspond to the XRD spectra of Comparative Examples 4 to 7 with different synthesis time and temperature conditions. Figure 2 As shown in a, the diffraction peaks of the XRD patterns of Comparative Examples 4 to 5 cannot be completely consistent with VO 2 This indicates that the expected product CaSr-VO with high purity cannot be obtained if the synthesis temperature is too low or too high. 2 . And from Figure 2 b shows that the diffraction peaks of the XRD patterns of Comparative Examples 6 to 7 are basically consistent with those of VO 2 The sample of Comparative Example 6 has poor crystallinity, while the sample of Comparative Example 7 has a rod-like structure ( Figure 3 ), indicating that if the synthesis time is too short or too long, the expected product CaSr-VO with good crystallinity and elongated ribbon morphology cannot be obtained. 2 .
[0071] Figure 4 a-4d correspond to the SEM images of Comparative Example 1 and Examples 1 to 3, respectively. Figure 4 It can be seen from a that the pure VO prepared by the method described in this application 2 It presents an uneven morphology structure, with short ribbons and large, stacked particles. This irregular morphology leads to the 2 The low specific surface area of the material limits its electrochemical active sites and thus reduces its zinc storage capacity. 2+ During the long-term cycle of insertion / removal, the product may break or deform. Figure 4 b, the microstructure of Example 1 has begun to change, showing more banded structures, but with a small amount of particles. Figure 4 c, a new morphology is shown. At this time, the morphology of the material is completely changed into a uniform, elongated ribbon structure, without particles and other morphologies. Moreover, the criss-crossed elongated ribbon structure is in the Zn 2+ Less prone to deformation during insertion / removal cycles. Figure 4 In d, it still shows an elongated ribbon morphology, but some of the ribbon structures show stacking phenomenon.
[0072] like Figure 5As shown in a, Example 2 is composed of V, O, Ca, and Sr elements. Among them, the XPS characteristic peaks of Ca 2p are located at 348.1eV and 351.7eV ( Figure 5 b), corresponding to Ca 2p 3 / 2 and Ca2p 1 / 2 ; The XPS characteristic peaks of Sr 3d are located at 134.3eV and 136.1eV ( Figure 5 c), corresponding to Sr 3d 5 / 2 and Sr 3d 3 / 2 These results confirm that Ca 2+ and Sr 2+ ions were successfully co-preintercalated into VO 2 The same results can be obtained by testing Examples 1 and 3.
[0073] It can be seen that the method described in the present application can achieve Ca by regulating the molar ratio of calcium sulfate and strontium sulfate. 2+ and Sr 2 + The ions are co-pre-embedded, and the material can present a special morphological structure without causing significant damage to the crystal structure of the material.
[0074] 2. Electrochemical performance
[0075] (1) Ca 2+ and Sr 2+ The three groups of embodiments and one group of comparative examples pre-embedded together were used as positive electrode materials for zinc ion batteries to assemble zinc ion batteries and compare their rate performance and cycle stability. The test data are as follows: Figure 6 As shown in a-6c.
[0076] from Figure 6 It can be seen that under the same test conditions, the specific capacities of Examples 1 to 3 at 0.1A / g are 410mAh / g, 442mAh / g and 491mAh / g respectively; at 10.0A / g, the specific capacities are still as high as 231mAh / g, 297mAh / g and 176mAh / g respectively, and the capacity retention rates are 56.3%, 67.2% and 35.8% at 0.1A / g respectively; when the current density is restored to 0.1A / g, the specific capacity is basically the same as the initial specific capacity. The specific capacity of the comparative example at 0.1A / g is only 359mAh / g; at 10.0A / g, the specific capacity drops to 154mAh / g, and the capacity retention rate is only 42.9% at 0.1A / g.
[0077] Example 2 exhibits the most excellent rate performance.
[0078] from Figure 6As can be seen from Figure b, after 100 cycles of charge and discharge at 0.1A / g, the specific capacity of Example 2 is still as high as 457mAh / g, and its capacity retention rate is as high as 96.4%; while under the same test conditions, after 95, 63 and 100 cycles of charge and discharge, the specific capacities of Example 1, Example 3 and Comparative Example 1 are 343mAh / g, 409mAh / g and 225mAh / g, respectively, and their capacity retention rates are only 82.8%, 76.5% and 63.9%, respectively. Example 2 shows more excellent stable specific capacity and cycle stability at a small current density of 0.1A / g.
[0079] Likewise, from Figure 6 As can be seen from Figure c, at 5.0 A / g, after 6000, 6000 and 4300 cycles, the specific capacities of Examples 1 to 3 were 146 mAh / g, 258 mAh / g and 130 mAh / g, respectively, and the capacity retention rate of Example 2 was as high as 73.6%. However, after 6000 cycles, the capacity of Comparative Example 1 was only 114 mAh / g, and the capacity retention rate was only 42.7%.
[0080] Example 2 also exhibits better cycle stability at a high current density of 5.0 A / g.
[0081] Compared with the examples and comparative examples with different concentrations of pre-embedded ions, Example 2 has more excellent stable specific capacity and rate performance, and has longer cycle stability at both a small current density of 0.1 A / g and a large current density of 5.0 A / g, which indicates that the co-pre-embedded concentration of Example 2 is the most suitable concentration and can obtain the best electrochemical performance.
[0082] (2) The two groups of comparative examples of the double ion co-pre-embedded embodiment and the single ion pre-embedded embodiment were used as positive electrode materials for zinc ion batteries to assemble zinc ion batteries and compare their rate performance and cycle stability. The test data are as follows: Figure 7 As shown in a-7b.
[0083] from Figure 7 It can be seen that under the same test conditions, the specific capacities of Comparative Examples 2 and 3 at 10.0 A / g are 298 mAh / g and 207 mAh / g, respectively, and the capacity retention rates are 71.8% and 45.4% at 0.1 A / g; when the current density is restored to 0.1 A / g, the specific capacity is basically the same as the initial specific capacity.
[0084] But from Figure 7 b It can be seen that after 2200 cycles of charge and discharge at 1.0 A / g, the specific capacity of Example 2 is as high as 292 mAh / g, and its capacity retention rate is 73.0%; while Comparative Examples 2 and 3 can only cycle 2000 and 987 times, respectively, and their capacity retention rates are only 61.4% and 69.4%, respectively.
[0085] Compared with the single ion pre-embedded comparative examples 2 and 3, Ca 2+ and Sr 2+ The co-pre-embedded Example 2 exhibited better rate capability and longer cycle stability, which indicated that the Ca 2+ and Sr 2+ Compared with Ca 2+ or Sr 2+ Single ion pre-embedding further increases VO 2 Rate performance and cycle stability of positive electrode materials.
[0086] (3) Four groups of comparative examples with different synthesis temperatures and synthesis time conditions were used for zinc ion battery positive electrode materials to assemble zinc ion batteries and compare their rate performance. The test data are as follows Figure 8 As shown in a-8b.
[0087] from Figure 8 It can be seen that under the same test conditions, the specific capacities of Comparative Examples 4 and 5 at 10.0 A / g are as low as 28 mAh / g and 2 mAh / g, respectively, and the capacity retention rates are 6.9% and 1.0% at 0.1 A / g, respectively; when the current density is restored to 0.1 A / g, the specific capacity decreases rapidly compared with the initial specific capacity.
[0088] from Figure 8 b It can be seen that under the same test conditions, the specific capacities of comparative examples 6 and 7 at 10.0 A / g are as low as 14 mAh / g and 11 mAh / g, respectively, and the capacity retention rates are 4.0% and 11.6% at 0.1 A / g, respectively; when the current density is restored to 0.1 A / g, the specific capacity decreases slightly compared with the initial specific capacity.
[0089] The capacity retention rate of Example 2 at 10.0 A / g is 67.2% of that at 0.1 A / g. Compared with Comparative Examples 4 to 7, Example 2 shows better rate performance, which indicates that the synthesis temperature and synthesis time of Example 2 are more suitable. Too high or too low a synthesis temperature or too long or too short a synthesis time will have a greater impact on its electrochemical performance.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing a dual-ion co-pre-embedded VO2 material, characterized in that: The specific steps include: Step 1: dissolving vanadium pentoxide in deionized water, adding calcium sulfate and strontium sulfate, and continuously stirring to obtain a mixed solution; wherein the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is (10-50):1:1; Step 2: adding ethylene glycol to the mixed solution obtained in step 1; wherein the molar ratio of the added amount of ethylene glycol to the vanadium pentoxide is (95:1) to (105:1); Step 3: placing the mixture obtained in step 2 in an autoclave and reacting at 160° C. to 200° C. for 10 h to 14 h; Step 4: Wash the product obtained from the reaction in step 3 to obtain CaSr-VO2 material.
2. The preparation method according to claim 1, characterized in that: In step 1, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is (10-20):1:
1.
3. The preparation method according to claim 2, characterized in that: In step 1, the molar ratio of vanadium pentoxide, calcium sulfate and strontium sulfate is 20:1:
1.
4. The preparation method according to claim 2, characterized in that: The CaSr-VO2 material has an elongated ribbon morphology.
5. The preparation method according to claim 1, characterized in that: In step 3, the reaction temperature is 180° C. and the reaction time is 12 h.
6. An application of a dual-ion co-pre-embedded VO2 material, characterized in that: The CaSr-VO2 nanobelt material prepared by any one of the preparation methods described in claims 1 to 5 is used as a positive electrode material for an aqueous zinc ion battery.